Knowledge management: an opportunity for the industrial production of software - Bianchi, Alejandro (2002)
This abstract explores the critical role of Knowledge Management (KM) in enhancing the industrial production of software. It emphasizes that learning capability is the key sustainable competitive advantage in today's dynamic global market. ​KM involves identifying, organizing, and disseminating both explicit and tacit knowledge within organizations to improve decision-making, efficiency, and quality. The ultimate goal is to achieve higher value-added products and services through efficient knowledge reuse and process maturity.